(untitled) (Multidisciplinary Journal of Science and Technology, 2025)
The vaginal microbiome plays a fundamental role in maintaining women’s reproductive health. A balanced microbiota, primarily dominated by Lactobacillus species, provides protection against infections, regulates vaginal pH, and supports fertility. However, dysbiosis—a disruption in microbial balance—can lead to bacterial vaginosis (BV), yeast infections, sexually transmitted infections (STIs), and even pregnancy complications. This article explores the composition of the vaginal microbiome, its interaction with the immune system, and its impact on gynecological and obstetric health. Emerging treatments, including probiotics and microbiome-targeted therapies, are also discussed.